Did the 2007 welfare reforms for low income parents in Australia increase welfare exits? - Yin King Fok; Duncan McVicar (IZA Journal of Labor Policy, 2013)
This paper examines the impacts of recent Australian welfare to work reforms for low-income parents of school-aged children who had been in receipt of Parenting Payment - the main welfare payment for this group - for at least one year. Specifically, the reforms introduced a requirement to engage in at least 15 hours of work-related activity per week from the youngest child's seventh birthday. As was the case for similar reforms introduced by US states in the 1990s, these reforms had large, statistically significant and positive impacts on the hazard rates for exiting the welfare payment. Two thirds of these exits were exits from welfare altogether and one third were exits to other welfare payments.
Keywords: I38; J22; 330; welfare reform; welfare to work; activation; lone parents; labour supply; Australia